Effect of brain death and donor treatment on organ inflammatory response and donor organ viability - Nijboer, W; Schuurs, T; Van Der Hoeven, J; Ploeg, R (2004)
These findings in brain death of an inflammatory response at organ level together with a first attempt of the organ to protect itself offer new opportunities in donor treatment and preservation. By focusing attention on the specific blocking or stimulating of these processes, graft survival may be enhanced. The first studies in this direction already show promising results for graft survival. © 2004 Lippincott Williams and Wilkins.